Study of two G-protein coupled receptor variants of human trace amine-associated receptor 5 - Wang, Xiaoqiang (Nature Publishing Group, 2011)
Here we report the study of two bioengineered variants of human trace amine-associated receptor 5 (hTAAR5) that were expressed in stable tetracycline-inducible HEK293S cell lines. A systematic detergent screen showed that fos-choline-14 was the optimal detergent to solubilize and subsequently purify the receptors. Milligram quantities of both hTAAR5 variants were purified to near homogeneity using immunoaffinity chromatography followed by gel filtration. Circular dichroism showed that the purified receptors had helical secondary structures, indicating that they were properly folded. The purified receptors are not only suitable for functional analyses, but also for subsequent crystallization trials. To our knowledge, this is the first mammalian TAAR that has been heterologously expressed and purified. Our study will likely stimulate in the development of therapeutic drug targets for TAAR-associated diseases, as well as fabrication of TAAR-based sensing devices.